Significance Aberrant Of CD133 Expression and Their Clinical Impact in Acute Lymphoblastic Leukemia among Sudanese Patients in Khartoum State - Elnour Atia, Ayman .E.; Hamid, Tarig A. M.; Elkarsany, Mubarak Mustafa; M. Mohamed, Samah Saif Eldin; Madani, Nadia M.; Bashir, Amro B. E. (International Journal of Innovative Research in Medical Science, 2021)
Background: Acute lymphoblastic leukemia (ALL) is a malignant disease that arises from several genetic mutations in a single B- or T-lymphoid precursor, resulting in altered blast cell survival, proliferation, and maturation. Objectives: This current study was aimed to determine the significance of aberrant CD133 and 45 expressions in Sudanese Patients with Acute lymphoblastic Leukemia, and their clinical significance in Khartoum state. Materials and Methods: One hundred Sudanese participants were enrolled in this study as follows: 88 Patients diagnosed with ALL as a case and 12 healthy controls donors were randomly selected. 2.5-5 mL of EDTA blood/bone marrow for flowcytometry from each patient and controls subject. Results: Eighty-eight newly diagnosed Sudanese patients with acute lymphocytic leukemia (ALL) were involved in this study, their age average is (15.7) and their stander deviation (SD) is 17.4. The frequency of aberrant markers concerning control groups was significantly associated with all patients in CD 45 with a P value (0.0001), while there was no difference between cases and control in the frequency of CD 133 antigen, there was no significant difference between age groups in the expression of different aberrant antigens. The study was significantly more expressed CD133 in males than females. Also no significant difference in hematological parameters between patients with or without expression of Aberrant CD 45 and 133 markers, while we found significantly high TWBCs in T. cell leukemia. Conclusion: Aberrant myeloid antigens CD45 was significantly associated with childhood and adult ALL and may be considered as important prognostic factors, while CD 133 were not associated with ALL.